Male Contraception - Abbe, Carmen R. (Yale J Biol Med, 2020)
Unintended pregnancy is a global public health problem. Despite a variety of female contraceptive options, male contraceptive options are limited to the condom and vasectomy. Condoms have high failure rates and surgical vasectomy is not reliably reversible. There is a global need and desire for novel male contraceptive methods. Hormonal methods have progressed the furthest in clinical development and androgen plus progestin formulations hold promise as a marketable, reversible male contraceptive over the next decade. Investigators have tested androgen plus progestin approaches using oral, transdermal, subdermal, and injectable drug formulations and demonstrated the short-term safety and reversibility of hormonal male contraception. The most commonly reported side effects associated with hormonal male contraception include weight gain, acne, slight suppression of serum high-density cholesterol, mood changes, and changes in libido. Efficacy trials of hormonal male contraceptives have demonstrated contraceptive efficacy rates greater than that of condoms. Although there has been less progression in the development of nonhormonal male contraceptives, potentially reversible vaso-occlusive methods are currently in clinical trials in some countries. Various studies have confirmed both men and women’s desire for novel male contraceptives. Barriers to development include an absence of investment from pharmaceutical companies, concerns regarding side effects and spermatogenic rebound with hormonal methods, and lack of clear reversibility and proven effectiveness of nonhormonal methods. The ultimate availability of male contraceptives could have an important impact on decreasing global unintended pregnancy rates (currently 40% of all pregnancies) and will be a step towards reproductive justice and greater equity in family planning.